Development and validation of a nomogram for predicting postoperative intraluminal hemorrhage in patients undergoing laparoscopic pancreaticoduodenectomy - Wang, Shuai; Li, Dongrui; Du, Chengxu; Yang, Xinda; Haitao, Lv (Frontiers in Surgery, 2025)
PurposeThis study aims to investigate the risk factors for postoperative intraluminal hemorrhage (IPPH) after laparoscopic pancreaticoduodenectomy (LPD), with the aim of enhancing clinical management through the exploration and development of a risk prediction model with those factors.MethodThe clinical data of 326 hospitalized patients between January 2020 and August 2023 who underwent LPD for malignancies were retrospectively selected. The data consisted of general conditions, comorbidities, preoperative treatments, laboratory tests, and postoperative complications. We explored the risk factors associated with postoperative intraluminal hemorrhage using univariate and multivariate logistic regression analyses and developed a predictive model of IPPH after LPD.ResultsThe incidence of IPPH in LPD patients was 7.06%. Advanced age (OR = 1.065, 95% CI = 1.001–1.133, P = 0.045), low fibrinogen level (OR = 0.485, 95% CI = 0.242–0.972, P = 0.041), low albumin level (OR = 0.840, 95% CI = 0.739–0.956, P = 0.008), clinically relevant postoperative pancreatic fistula (CR POPF, OR = 4.300, 95% CI = 1.347–13.722, P = 0.014), and intra-abdominal infection (IAI, OR = 6.347, 95% CI = 1.454–27.716, P = 0.014) were associated with an increased incidence of IPPH. A nomogram was developed and validated with a specificity of 82.2%, a sensitivity of 82.6%, and an AUC value of 0.861 (95% CI 0.783–0.939).ConclusionRisk factors for IPPH include advanced age, low fibrinogen levels, low albumin levels, CR POPF, and IAI. These risk factors were used to develop a nomogram for identifying patients at high risk of IPPH, allowing for targeted interventions to address modifiable risk factors promptly and improve patient outcomes.